Suppression of defects in cyclic adenosine 3',5'-monophosphate metabolism in Escherichia coli. - Alexander, J K (1980)
Strain MM6-13 (ptsI suc lacI sup) of Escherichia coli contains a suppressor of the succinate-negative phenotype. In MM6-13, sup caused enhanced growth in glycerol, maltose, melibiose, and succinate media and increased activity of beta-galactosidase and tryptophanase relative to an isogenic strain without sup. In strain A61 (cya sup), sup partially suppressed cya. Cyclic guanosine monophosphate increased beta-galactosidase activity sevenfold in A61 and enabled this strain to grow on maltose, galactose, succinate, and arabinose. Strain A61 responded to much lower concentrations of cyclic adenosine monophosphate than cyclic guanosine monophosphate. It appears that sup is located in the crp locus. These results suggest that sup mutants have an altered cyclic adenosine monophosphate receptor protein which is activated by cyclic guanosine monophosphate and has an increased affinity for cyclic adenosine monophosphate.